The Hollywood sign : fantasy and reality of an American icon - Braudy, Leo (Icons of America., 2011)
"Hollywood's famous sign, constructed of massive white block letters set into a steep hillside, is an emblem of the movie capital it looms over and an international symbol of glamour and star power. To so many who see its image, the sign represents the earthly home of that otherwise ethereal world of fame, stardom, and celebrity--the goal of American and worldwide aspiration to be in the limelight, to be, like the Hollywood sign itself, instantly recognizable. How an advertisement erected in 1923, touting the real estate development Hollywoodland, took on a life of its own is a story worthy of the entertainment world that is its focus. Leo Braudy traces the remarkable history of this distinctly American landmark, which has been saved over the years by a disparate group of fans and supporters, among them Alice Cooper and Hugh Hefner, who spearheaded its reconstruction in the 1970s. He also uses the sign's history to offer an intriguing look at the rise of the movie business from its earliest, silent days through the development of the studio system that helped define modern Hollywood. Mixing social history, urban studies, literature, and film, along with forays into such topics as the lure of Hollywood for utopian communities and the development of domestic architecture in Los Angeles, The Hollywood Sign is a fascinating account of how a temporary structure has become a permanent icon of American culture"--Publisher